PENGARUH PENGGANTIAN KOIL SEPEDA MOTOR GL 100 DENGAN KOIL MOBIL LAND ROVER TERHADAP KONSUMSI BAHAN BAKAR - Aryananta Lufti; Santoso, Edy Budi; Nurtjahyono (JURNAL MEKANIKASISTA, 2025)
The ignition coil in a motorcycle functions to increase the electrical voltage from a 12-volt battery to thousands of volts, which is then delivered to the spark plug to generate a spark for the combustion process. This study analyzes the effect of replacing a motorcycle ignition coil with a car ignition coil on fuel consumption. The experiment was conducted using several variables, including engine speed, fuel consumption time, and power output. The results indicate that an engine using a car ignition coil produces greater power than one using a motorcycle coil, while also being more fuel-efficient. This is due to the stronger and more efficient ignition provided by the car coil, which enhances combustion efficiency and reduces fuel wastage